2013
DOI: 10.1038/bmt.2013.112
|View full text |Cite
|
Sign up to set email alerts
|

Oral ribavirin for treatment of respiratory syncitial virus and parainfluenza 3 virus infections post allogeneic haematopoietic stem cell transplantation

Abstract: The prognosis for patients with respiratory syncytial virus (RSV) or parainfluenza virus type 3 (PIV3) respiratory tract infection post allogeneic haematopoietic progenitor cell transplant (HPCT) is historically poor. The use of oral ribavirin (RBV) has not been widely studied in this patient population. We examined the outcomes of 15 consecutive patients (RSV, n ¼ 13 and PIV3, n ¼ 2) treated with oral RBV post HPCT. Oral RBV was commenced at a starting dose of 10 mg/kg/day, increasing to a maximum dose of 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 28 publications
(42 reference statements)
0
41
2
Order By: Relevance
“…The current case series demonstrates acceptable tolerability in three children and one young adult with lower respiratory tract infection. The most common side effects reported with oral ribavirin include hemolytic anemia and elevation of transaminases . The most common adverse effect in our case series was hemolytic anemia, which necessitated transfusion in 2 patients.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The current case series demonstrates acceptable tolerability in three children and one young adult with lower respiratory tract infection. The most common side effects reported with oral ribavirin include hemolytic anemia and elevation of transaminases . The most common adverse effect in our case series was hemolytic anemia, which necessitated transfusion in 2 patients.…”
Section: Discussionmentioning
confidence: 80%
“…Although data regarding the concentration of systemic ribavirin in lung tissue or BAL fluid are lacking, a retrospective study detected no significant differences in 6‐month outcomes between oral and inhaled ribavirin therapy for RSV infection after lung transplantation . Since oral ribavirin can be continued in an outpatient setting, it is also associated with reduced length of hospital stays when compared with the aerosolized form …”
Section: Discussionmentioning
confidence: 99%
“…12 However, it has been hypothesised that oral administration may not prevent progression of the infection, and consequently suggested that treatment starts with a high dose that is later escalated according to how the patient responds. 13 The appropriate duration of treatment has yet to be established, although most groups continue pharmacological therapy until the virus is cleared. The combination of antiviral agents with the monoclonal antibody palivizumab is safe, well-tolerated by the patient, and has shown high efficacy in association with symptom resolution and viral clearance.…”
Section: Discussionmentioning
confidence: 99%
“…8 SCID is usually fatal without restoration of immune function by BMT or gene therapy. 14,15 P. jiroveci is an opportunistic pathogen which can cause infection and death in children with patients with severe T-cell immunodeficiencies. 9 Treatment of RSV infection in immunocompromised patients includes RBV, palivizumab and IVIG.…”
Section: Discussionmentioning
confidence: 99%